[PP.36.16]: CHOICE OF ANTICOAGULATION THERAPY IN PATIENTS WITH ATRIAL FIBRILLATION FOLLOWED AT TERTIARY ARTERIAL HYPERTENSION A CHRONIC HEART FAILURE CLINICS. (June 2015) - Málek>, F.>; Vondrakova, D.; Dvorak, J.; Matouskova, J.; Rokyta, K.; Pintar, F.; Neuzil, P.
Abstract : Objective: Prescribing of novel anticoagulation therapy (NOAC) is expensive and is limited by the rules of insurance company. The study objective was to evaluate other factors infuenting the choice of NOAC u the patients with atrial fibrillation and arterial hypertension and chronic heart failure. Design and method: Clinical and laboratory parameters, and CHADS2, CHADS VASc and HAS-BLED scores were analyzed and calculated in a cohort of consecutive patients having a regular follow-up visit at tertiary care arterial hypertension a chronic heart failure clinics. Of 89 subject, total number of 52 subjects were indicated to NOAC (group N) and 37 patients stayed on warfarin (W). Results: Mean age in N was 69 years and 73 in W (p = 0.024), with higher proportion of patients > 75 years in W group (p = 0.021). There was higher prevalence of heart failure and vascular disease in group W compared to N (92 % vs. 77 % p = 0.048 and 70 % vs. 48% p = 0.035 respectively). Patients N had lower risk of stroke (CHADS2 score 2, 4 vs. 3.0, p = 0.02, CHADS-VASc 3.75 vs. 4.70, p = 0.011) but higher risk of bleeding (HAS-BLED (2.55 vs. 2.13, p = 0.049). Patients from W group had lower ejection fraction (LV EF, 41 vs 49%, p = 0.038), higher creatinine level (p = 0.042), lower estimated glomerular filtration rate (eGFR, p = 0.017) and lower mean hemoglobin level (p = 0.018). CHADS2 score correlated with body mass index (BMI, r = 0.477) and LV EF (r = −0.659) and HAS-BLED score correlated with eGFR (r = −0.442) only in N group. Conclusions: Patients indicated for NOAC were surprisingly younger, with lower prevalence of heart failure and vascular disease, with lower risk of stroke but significantly higher risk of bleeding than patients continuing warfarin therapy. BMI, LV EF and eGFR are other parameters which should be used in the decision making in the choice of anticoagulation therapy.